2010
DOI: 10.1111/j.1750-3841.2009.01407.x
|View full text |Cite
|
Sign up to set email alerts
|

α‐Mangostin, A Novel Dietary Xanthone, Suppresses TPA‐Mediated MMP‐2 and MMP‐9 Expressions through the ERK Signaling Pathway in MCF‐7 Human Breast Adenocarcinoma Cells

Abstract: This study first investigates the anti-metastatic effect of alpha-mangostin on 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced matrix metalloproteinase-2 (MMP-2) and matrix metalloproteinase-9 (MMP-9) expressions in human breast adenocarcinoma cells, MCF-7. First, the result demonstrated alpha-mangostin could inhibit TPA-induced abilities of the adhesion, invasion, and migration by cell-matrix adhesion assay and Boyden chamber assay. Data also showed alpha-mangostin could inhibit the activation of extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 38 publications
4
49
0
Order By: Relevance
“…Many studies have revealed α-MGʼs inhibitory activities against invasion and migration of cancer cells, and the inhibition of NF-κB is one of the most important mechanisms for its antimetastatic effects. For example, α-MG exhibited a significant antimetastatic effect against TPA-stimulated human breast cancer MCF-7 cells through the inhibition of nuclear translocation and DNA binding activity of NF-κB via blocking phosphorylation and degradation of IκBα [117]. It has been reported that functions mediated by NF-κB are at least partially performed in cooperation with STAT3.…”
Section: Inhibition Of Survival Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have revealed α-MGʼs inhibitory activities against invasion and migration of cancer cells, and the inhibition of NF-κB is one of the most important mechanisms for its antimetastatic effects. For example, α-MG exhibited a significant antimetastatic effect against TPA-stimulated human breast cancer MCF-7 cells through the inhibition of nuclear translocation and DNA binding activity of NF-κB via blocking phosphorylation and degradation of IκBα [117]. It has been reported that functions mediated by NF-κB are at least partially performed in cooperation with STAT3.…”
Section: Inhibition Of Survival Pathwaysmentioning
confidence: 99%
“…Despite showing an improved water solubility, all of them reduced the activity of the parent compound. Aisha et al [138] prepared solid dispersions of α-MG in PVP that showed improved solubility, self-assembly of nanomicelles, and intracellular delivery through endocytosis, ▶ MMP-2/MMP-9 expression↓, ERK1/2↓, IκBα degradation↓, nuclear levels of NF-κB/AP-1↓, NF-κB/AP-1 DNA binding↓ TPA-induced human brest MCF-7 cells [117] pNF-κB/p65Ser552↓, pStat3Ser727↓, pStat3Tyr705↓, MMP9↓, DNA binding activity of NF-κB/Stat3↓, TIMP1 expression↑…”
Section: Molecular Modeling and Docking Studymentioning
confidence: 99%
“…Breast cancer is the most common female malignancy and the second leading cause of cancer mortality worldwide (1). Invasion and metastasis are fundamental properties of malignant cancer cells and primary factors that promote cancer progression (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Invasion and metastasis are fundamental properties of malignant cancer cells and primary factors that promote cancer progression (2,3). The invasion and metastasis of cancer cells involve multistep biological processes and various cytophysiological changes including the degradation of tissue barriers such as the extracellular matrix (ECM) and basement membrane (1,3). ECM degradation and remodeling require the action of proteolytic enzymes, along with matrix metalloproteinases (MMPs) (1,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation